Analysis of Acceptability of Photosynthesis Material Teaching Module Based on Project Based Learning for NS Learning for Grade IV Elementary Schools - Agam Aris Munandar; Dede Tri Kurniawan; Yunus Abidin (CV. Ksatria Siliwangi, 2025)
This study aims to analyze the acceptability of a teaching module on photosynthesis material based on Project-Based Learning (PBL) for Natural Science (NS) learning in Grade IV elementary schools. The module was developed to enhance student engagement, self-regulation, and goal orientation in learning. The research employed a quantitative approach using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method to examine the relationships among user activity, user self-control, and goal orientation. Data were collected through questionnaires administered to teachers and students, focusing on their perceptions and experiences with the teaching module. The results indicate a significant positive relationship between user activity and user self-control, which collectively influence goal orientation. These findings suggest that the PBL- based module effectively supports active learning and self-regulated behaviors, ultimately fostering goal-oriented learning outcomes. This research provides valuable insights for educators and curriculum developers to design innovative instructional materials that promote active and independent learning in elementary education.